The Role of Digitalization on the Internationalization Strategy of Born-Digital Companies - Vadana Ioan-Iustin; Kuivalainen Olli; Torkkeli Lasse; Saarenketo Sami (MDPI, 2022)
Digital technologies have led to born-digital companies, defined by their highly digitalized value chains, designed at their inception. Born-digital (BD) companies leverage digitalization across their value chains in the internationalization path. However, despite this emergence, very few empirical studies in international business literature have explained the impact of bricolage in conducting value chain activities and exploiting the internationalization strategy of BD companies. The present study responds to these omissions of how the digitalization of the value chain activities and the internationalization strategy enhance companies by allowing them to reach customers (users) and partners with available resources and less time. The results indicate that the digitalization of value chain activities facilitates the re-use and mixing of the resources at hand to overcome challenges, innovate solutions, or create new opportunities for international growth, in line with the bricolage theory. Overall, this study contributes to international business literature regarding, specifically, the behaviors of born-digital companies as they strategically approach internationalization efforts.